Visual Profile of Motorcycle-related Ocular Trauma in a Tertiary Hospital - Allan Joseph L. Larona, MD; Mary Rose L. Pe-Yan, MD (Philippine Journal of Ophthalmology)
Objectives: To provide a representative data on the local profile of motorcycle-related ocular trauma seen in a tertiary hospital over a period of one year.